2017
DOI: 10.3390/brainsci7020015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Hand Pain on Training-Induced Changes in Motor Performance and Corticospinal Excitability

Abstract: Pain influences plasticity within the sensorimotor system and the aim of this study was to assess the effect of pain on changes in motor performance and corticospinal excitability during training for a novel motor task. A total of 30 subjects were allocated to one of two groups (Pain, NoPain) and performed ten training blocks of a visually-guided isometric pinch task. Each block consisted of 15 force sequences, and subjects modulated the force applied to a transducer in order to reach one of five target forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…For instance, during training of a novel tongue-protrusion task, it was shown that capsaicin cream applied to the tongue reduced the gains in excitability of the tongue MI that would otherwise occur during training in a pain-free state, however, gains in performance were still evident [ 9 ]. A later study corroborated that pain can interfere with corticomotor excitability increases, but not necessarily acquisition of the motor skill [ 40 ]. It has further been reported that if pain affects acquisition of movement patterns during training, these altered movement patterns may persist 24 hours later [ 41 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, during training of a novel tongue-protrusion task, it was shown that capsaicin cream applied to the tongue reduced the gains in excitability of the tongue MI that would otherwise occur during training in a pain-free state, however, gains in performance were still evident [ 9 ]. A later study corroborated that pain can interfere with corticomotor excitability increases, but not necessarily acquisition of the motor skill [ 40 ]. It has further been reported that if pain affects acquisition of movement patterns during training, these altered movement patterns may persist 24 hours later [ 41 ].…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, neck training in the presence of acute hypertonic saline-induced pain may induce long-lasting inhibition of corticomotor excitability [ 42 ]. Conversely, other studies have reported that different topical pain paradigms such as capsaicin [ 40 , 43 45 ] or heat [ 46 ] do not alter acquisition during performance of different motor tasks, but retention may be enhanced [ 45 ]. As such, a large body of contrasting evidence is available, and the interaction between pain and motor acquisition/retention remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS) has been commonly used to investigate the effect of experimental pain on corticospinal excitability. Together, TMS studies show no consensus and it has been reported that pain can either induce a decrease [ 18 24 ] and increase [ 25 27 ] or have no effect [ 16 , 28 30 ] on corticospinal excitability. This might be attributed, at least in part, to several methodological differences between studies.…”
Section: Introductionmentioning
confidence: 99%
“…The modality appears to matter more that the pain intensity, as average pain ratings are comparable across studies using topical capsaicin cream [49][50][51][52][53] and intramuscular hypertonic saline injection [12,13,16]. Importantly, several previous studies using experimental cutaneous pain demonstrated modulations of corticospinal excitability [6,[49][50][51][52] and alterations of motor performance [54] and motor learning [55,56]. Therefore, the present results should not be interpreted as indicating that cutaneous pain does not interact with the motor system, but rather that in the case of cutaneous pain, these interactions appear to occur at the cortical level rather than at the spinal level.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the large brain network which is classically associated with pain processing (including the primary and secondary somatosensory, insular, and anterior cingulate and prefrontal cortices and thalamus), some functional neuroimaging studies have reported hemodynamic changes in brain regions related to motor function during pain, including the primary motor cortex [ 58 60 ]. As mentioned in Introduction, many transcranial magnetic stimulation studies also showed a pain-induced modulation of corticospinal excitability [ 6 , 49 51 ], with some studies showing alterations in mechanisms which are known to be intracortical, such as short-interval intracortical inhibition [ 61 63 ] and interhemispheric inhibition [ 64 ]. Only a few transcranial magnetic stimulation studies examined the effect of pain specifically on circuits involved in sensorimotor integration, which is relevant to EV responses.…”
Section: Discussionmentioning
confidence: 99%